The Effect of Early Noncognitive Skills on Social Outcomes in Adolescence - Katja Coneus; Manfred Laucht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper investigates the impact of early noncognitive skills on social outcomes in adolescence. The child's attention span, approach, prevailing mood and distractibility in early childhood may be crucial predictors for school achievements, health risk behavior, delinquency and autonomy as adolescent. We investigate this issue using a longitudinal epidemiological cohort study of 384 children at risk from the Rhine-Neckar Region in Germany. Our results indicate that noncognitive skills in early childhood are important predictors of educational success, tobacco and alcohol use, delinquency and autonomy in adolescence. In particular, the attention span has emerged as a dominant factor among noncognitive skills regarding educational performance, health behavior and delinquency in our study. Further, we find that boys with low noncognitive skills have significantly lower social outcomes compared to girls.
Keywords: J24; J13; I20; 330; noncognitive skills; early childhood; risk factors; social outcomes; Kinder; Soziales Verhalten; Emotion; Jugendliche; Persönlichkeitspsychologie; Bildungsniveau; Deutschland